2012
DOI: 10.3945/ajcn.111.023036
|View full text |Cite
|
Sign up to set email alerts
|

Relation between holiday weight gain and total energy expenditure among 40- to 69-y-old men and women (OPEN study)

Abstract: A high preholiday absolute TEE or residual TEE did not protect against BW gain during the winter holiday quarter. It is not known whether higher than these typical TEE levels would protect against weight gain or if the observed gain may be attributed to increased food consumption and/or reduced physical activity during the holiday quarter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
4
26
1
Order By: Relevance
“…This is consistent with other studies; in which a weight gain of less than 0.5 kg during this period was reported [3,8,12,13]. Only in the study of Reid and Hackett a 0.93 kg weight gain was reported in subjects [14].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies; in which a weight gain of less than 0.5 kg during this period was reported [3,8,12,13]. Only in the study of Reid and Hackett a 0.93 kg weight gain was reported in subjects [14].…”
Section: Discussionsupporting
confidence: 93%
“…2003; Cook et al. 2012). Briefly, the primary purpose of the study was to assess error in self‐reported dietary data using doubly labeled water (DLW) for total energy expenditure (TEE) and urinary nitrogen for protein intake.…”
Section: Methodsmentioning
confidence: 99%
“…2003; Cook et al. 2012). Three post‐dose urine specimens were collected over the next 2–4 h and analyzed by isotope ratio mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The relatively small effect may occur because caloric intake fluctuates over time, which limits the predictive validity of habitual intake from only a 2-week observational period. Indeed, there is evidence that weight gain often occurs more over the holidays and on weekends versus on weekdays (Cook, Subar, Troiano, & Schoeller, 2012), suggesting that it might be necessary to collect serial measures of objectively measured caloric intake to more accurately predict future weight gain based on caloric intake.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have not found a significant relation between EE and future weight gain (Tataranni et al, 2003; Cook et al, 2012; Stunkard, Berkowitz, Stallings, & Schoeller, 1999; Goran et al, 1998; Luke et al, 2009), others have shown a positive relation between EE and future weight gain, indicating that higher, rather than lower EE is related to weight gain (Goran et al, 1998; Schoeller, 2008; Stunkard, Berkowitz, Schoeller, Maislin, & Stallings, 2004; Luke et al, 2007). In our sample, there was a significant positive correlation between DLW estimated EE and EI ( r = .71), and when EE is entered into the same linear mixed effects model instead of EI, it showed a significant positive relation to future weight gain ( t (202) = 2.10, p = .04, r = .15).…”
Section: Discussionmentioning
confidence: 99%